Vivências nas Territorialidades Transfronteiriças do Iguassu (TTI) - Derrosso, Giuliano Silveira (2018)
The objective of this research is to understand how transboundary experiences occur in the TTI - Transboundary Territorialities of Iguassu, encompassing the border between Foz do Iguaçu (BR), Ciudad del Est (PY) and Puerto Iguazú (AR). Based on this principle, documentary research was carried out to analyze the development process of territoriality in its economic, geographic, political and social aspects and semi-structured interviews individuals born in the border establishes relationships between cross-border living and aspects related to territoriality. As a theoretical contribution, authors from different areas of knowledge were used to discuss the concept of territoriality, borders and cross-border. From that point on, evidence was presented of the constitution of a transboundary territoriality, emphasizing the aspects of integration in the relationship between the three countries of the border. And in the same way that this integration will be observed in social economic aspects, it was possible to establish the parameters of a cross-border living, an experience built in the daily life of a territoriality where the individual's perception of borders is not related to the limits imposed by the states -nation. As characteristics of this cross-border living one can observe the aspects of the multiperience, of the multipropriations of identity, of the mobility-freedom binomial, of adaptability and flexibility, of the sense of universality, of approximations and confrontations, and of being-between. All these conditions point to the existence of specific characteristics of a transformer life based on diversity and tolerance of the other and built in the daily life of the inhabitants of this territoriality. From the point of view of individuals, the boundaries are not perceived as a limit, but rather as opportunities for (dis) encounters, confrontations, approximations, and especially of ongoing (de) identifications that favor a greater approximation to the more tolerant, diverse and universal.